Fabrication of junction-free Cu nanowire networks via Ru-catalyzed electroless deposition and their application to transparent conducting electrodes. (18th November 2021) - Song, Jinkyu; Kim, Mee-Ree; Kim, Youngtae; Seo, Darae; Ha, Kyungryul; Song, Tae-Eun; Lee, Wan-Gyu; Lee, Yonghee; Kim, Ki-Chul; Ahn, Chi Won; Han, Hee
Abstract: Over the past few years, metal nanowire networks have attracted attention as an alternative to transparent conducting oxide materials such as indium tin oxide for transparent conducting electrode applications. Recently, electrodeposition of metal on nanoscale template is widely used for formation of metal network. In the present work, junctionless Cu nanowire networks were simply fabricated on a substrate by forming a nanostructured Ru with 80 nm width as a seed layer, followed by direct electroless deposition of Cu. By controlling the density of Ru nanowires or the electroless deposition time, we readily achieve desired transmittance and sheet resistance values ranging from ∼1 kΩ sq −1 at 99% to 9 Ω sq −1 at 89%. After being transferred to flexible substrates, the nanowire networks exhibited no obvious increase in resistance during 8000 cycles of a bending test to a radius of 2.5 mm. The durability was verified by evaluation of its heating performance. The maximum temperature was greater than 180 °C at 3 V and remained constant after three repeated cycles and for 10 min. Transmission electron microscopy and x-ray diffraction studies revealed that the adhesion between the electrolessly deposited Cu and the seed Ru nanowires strongly influenced the durability of the core–shell structured nanowire-based heaters.